UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PUISI DENGAN PENERAPAN COOPERATIVE LEARNING SISWA KELAS IV SDN. 323 SINUNUKAN II - Elis Sobariah (Universitas Negeri Medan, 2016)
Abstract: Efforts to improve kemampuann Reading Poetry, with Implementation Implementation cooperative learning (Coorporatif Learning) fourth grade students of SD Negeri 323 Sinunukan II